From Coordination to Integration: Explaining Flood Governance Performance in Greater Jakarta’s Ciliwung-Cikeas-Cisadane Watersheds - Rahmat Salam; Izzatusholekha; Tria Patrianti; Nur Muhamad Iqbal (Department of Public Administration, 2026)
This study examines why flood control efforts in Greater Jakarta consistently underperform despite substantial investments and formal coordination mechanisms. Focusing on the Ciliwung, Cikeas, and Cisadane watersheds, it assesses an integrated governance approach framed as